Effect of Si on the oxidation reaction of α-Ti(0 0 0 1) surface: ab initio molecular dynamics study. Issue 1 (31st December 2017) - Bhattacharya, Somesh Kr.; Sahara, Ryoji; Ueda, Kyosuke; Narushima, Takayuki
Abstract: We present our ab initio molecular dynamics (MD) study of the effect of Si on the oxidation of α-Ti(0  0  0  1) surfaces. We varied the Si concentration in the first layer of the surface from 0 to 25 at.% and the oxygen coverage ( θ ) on the surface was varied up to 1 monolayer (ML). The MD was performed at 300, 600 and 973 K. For θ  = 0.5 ML, oxygen penetration into the slab was not observed after 16 ps of MD at 973 K while for θ  > 0.5 ML, oxygen penetration into the Ti slab was observed even at 300 K. From Bader charge analysis, we confirmed the formation of the oxide layer on the surface of the Ti slab. At higher temperatures, the Si atoms diffused from the first layer to the interior of the slab, while the Ti atoms moved from second layer to the first layer. The pair correlation function shows the formation of a disordered Ti-O network during the initial stage of oxidation. Si was found to have a strong influence on the penetration of oxygen in the Ti slab at high temperatures. Abstract :